Sex-dependent differences in behavioral and immunological responses to antibiotic and bacteriophage administration in mice - Grabowski, Łukasz; Pierzynowska, Karolina; Kosznik-Kwaśnicka, Katarzyna; Stasiłojć, Małgorzata; Jerzemowska, Grażyna; Węgrzyn, Alicja; Węgrzyn, Grzegorz; Podlacha, Magdalena (Frontiers in Immunology, 2023)
The problem of antibiotic resistance is a global one, involving many industries and entailing huge financial outlays. Therefore, the search for alternative methods to combat drug-resistant bacteria has a priority status. Great potential is seen in bacteriophages which have the natural ability to kill bacterial cells. Bacteriophages also have several advantages over antibiotics. Firstly, they are considered ecologically safe (harmless to humans, plants and animals). Secondly, bacteriophages preparations are readily producible and easy to apply. However, before bacteriophages can be authorized for medical and veterinary use, they must be accurately characterized in vitro and in vivo to determinate safety. Therefore, the aim of this study was to verify for the first time the behavioral and immunological responses of both male and female mice (C57BL/6J) to bacteriophage cocktail, composed of two bacteriophages, and to two commonly used antibiotics, enrofloxacin and tetracycline. Animal behavior, the percentage of lymphocyte populations and subpopulations, cytokine concentrations, blood hematological parameters, gastrointestinal microbiome analysis and the size of internal organs, were evaluated. Unexpectedly, we observed a sex-dependent, negative effect of antibiotic therapy, which not only involved the functioning of the immune system, but could also significantly impaired the activity of the central nervous system, as manifested by disruption of the behavioral pattern, especially exacerbated in females. In contrast to antibiotics, complex behavioral and immunological analyses confirmed the lack of adverse effects during the bacteriophage cocktail administration.